Thermal comfort guidelines for production spaces within multi-storey garment factories located in Bangladesh. (15th June 2019) - Hossain, Md Mohataz; Wilson, Robin; Lau, Benson; Ford, Brian
Abstract: This research presents extensive field data on indoor thermal conditions along with workers' comfort votes taken at their workstations within three existing multi-storied garment factories during the three seasons (cool-dry, hot-dry and warm-humid) of Bangladesh. The main objective of the study was to observe the impact of thermal conditions on workers' indoor thermal perception during each season of a year and from this identify thermal comfort guidelines (e.g. neutral temperatures, comfort ranges, preferred airspeeds and directions) to execute their production work comfortably. Subjective votes were collected from a total of 908 workers with the thermal data, physiological data and adaptive measures recorded simultaneously. Statistical analyses revealed that workers can accept a wider and relatively higher comfort range than the predicted band during cool-dry and hot-dry seasons, for instance, 22.7–29.1 °C and 22.3–30.4 °C respectively. A narrower comfort band (e.g. 28.7–30.9 °C), close to the predicted range, was found during the warm-humid season, which can be maintained by reducing radiant temperature and elevating airspeed. Further analyses indicated that workers prefer a mean airspeed of 0.3 m/s and comfort range of 0–3.0 m/s specific to their activities preferably from inlets located on south, north and east facades while upward and downward air movement, from for example ceiling fans, causes a rise of air temperature in the occupational zone and thermal discomfort. This research also suggested that the maximum distances of workstations from the ventilation inlets (windows) should be maintained at 12–18 m for sufficient cross ventilation, personal controls and adaptive opportunities to help maintain preferred thermal condition. Highlights: Workers adapt with wider comfort ranges during the cool-dry and hot-dry seasons. Favoured air temperature and airspeed ranges for production activities were determined. Upward and downward airflows increase air temperature and thermal discomfort. Workers prefer airflow from the inlets located in north and south facades. The width of workspaces should be between 12m and 18m to enhance thermal comfort.